2008
DOI: 10.1124/mol.108.048405
|View full text |Cite
|
Sign up to set email alerts
|

Patupilone-Induced Apoptosis Is Mediated by Mitochondrial Reactive Oxygen Species through Bim Relocalization to Mitochondria

Abstract: Among the new microtubule-targeted agents, the epothilone family of molecules has shown promising anticancer potential, and clinical trials are currently underway for patupilone (epothilone B) in various cancer indications. In this study, we characterized novel aspects of patupilone's cellular action that may underlie its potent cytotoxicity in human neuroblastoma cells. Patupilone induced mitochondrial membrane potential collapse, mitochondrial morphological changes, and cytochrome c release, leading to apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…It is well-known that p53 expression is induced by different anti-cancer drugs, including MTAs [6][7]. Consistently with this and our previous data [20], the present study showed that VRL increased the amount of cellular p53 and its target gene p21 that reflects p53 functionality.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is well-known that p53 expression is induced by different anti-cancer drugs, including MTAs [6][7]. Consistently with this and our previous data [20], the present study showed that VRL increased the amount of cellular p53 and its target gene p21 that reflects p53 functionality.…”
Section: Discussionsupporting
confidence: 93%
“…It depolymerises the microtubule network and leads to apoptosis after cell cycle arrest. Like other MTAs, it activates the intrinsic mitochondrial apoptotic pathway [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…After 30 minutes of H 2 -DCF-DA (10 µM) incubation in white medium, the formation of DCF fluorescent product was measured in a Fluoroskan Ascent (Thermo Fisher Scientific) microplate fluorometer (510 nm excitation, 580 nm emission), as previously described. 44 …”
Section: Measurement Of Reactive Oxygen Speciesmentioning
confidence: 99%
“…6,54 Treatment of human cancer cells with low nanomolar concentrations of Epo B produces aberrant mitotic spindles, results in cell cycle arrest in mitosis, and eventually leads to apoptotic cell death. 4,16 IC 50 s for cancer cell growth inhibition are in the nanomolar or even sub-nanomolar range, depending on the specific cell type, 4,16,18 In addition, apoptosis induction by Epo B has been suggested to involve the formation of reactive oxygen species in mitochondria; 55 it has also been linked to the activation of the nuclear translocation of the transcription factor NFkB in a process that would be independent of the microtubule effects of the compound. 56 The true significance of these findings for the antitumor activity of Epo B still needs to be established.…”
Section: Epothilone Bmentioning
confidence: 99%